Garba Dance Is Effective in Parkinson’s Disease Patients: A Pilot Study - Anish Mehta; Pooja Dugani; Rohan Mahale; null Nandakumar; Krishna Haskar Dhanyamraju; R. Pradeep; Mahendra Javali; Purushottam Acharya; R. Srinivasa (Parkinson's Disease, 2024)
Background. Dance as therapy is gaining attention as an adjuvant option for Parkinson’s disease (PD). Assessing culturally popular dance forms is crucial for promoting the acceptance of dance therapy in a culturally sensitive context. Objectives. The pilot study evaluated the efficacy of Garba dance for alleviating motor symptoms, nonmotor symptoms, cognitive functions, and mood. Furthermore, this pilot study also assessed the tolerability and safety of this dance form using fatigue severity scale and assessing falls, respectively. Methods. Eligible participants with mild-to-moderate PD (H&Y stage 1 to 2.5) were sequentially randomized into the dance therapy, physical therapy, or control groups. Motor symptoms, nonmotor symptoms, cognitive functions, and mood were assessed using standard scales at baseline, week 6, and week 12. Tolerability was measured using the Fatigue Severity Scale, and safety was assessed by monitoring falls. Results. In the Garba dance group, significant improvements in UPDRS scores were observed at week 6 (p=0.002) and week 12 (p<0.001) compared to baseline. At week 12, UPDRS scores were better in the Garba dance group as compared to the control and physical therapy groups. Freezing of gait significantly improved at week 6 (p<0.001) and week 12 (p<0.001) in the Garba dance group. Garba dance also led to significant improvements in mood and sleep. Tolerability was favorable, with significantly better fatigue severity scores in the Garba dance group at week 12 compared to controls and physical therapy. About 6 patients in Garba dance group experienced near falls. Conclusion. Underscoring a cautious optimism, results of the current study indicate that Garba dance may be an effective, safe, and well-tolerated intervention for Indian patients with mild-to-moderate PD (H&Y stage 1 to 2.5).